Analysis of the insertion/deletion related polymorphism within T cell antigen receptor β variable genes in primary Sjögren's syndrome. Issue 3 (11th February 2005) - Lawson, C A; Donaldson, I J; Bowman, S J; Shefta, J; Morgan, A W; Gough, A; Isaacs, J D; Griffiths, B; Emery, P; Pease, C T; Boylston, A W
Abstract : Objective: To analyse T cell receptor β variable (TCRBV) gene polymorphisms (insertion/deletion related polymorphism (IDRP) and BV6S7) in primary Sjögren's syndrome (PSS). Methods: Genomic DNA was extracted from blood samples from patients fulfilling the modified European criteria for PSS (n = 61). Healthy control blood samples were obtained from the Blood Transfusion Service (n = 121). As a disease control group, samples from patients with systemic lupus erythematosus (n = 42) were analysed. BV6S7 was genotyped using an established PCR/RFLP method. The IDRP was determined by comparison of the intensity of PCR product bands from within BV9S2 and an internal control region (BV9S1), to ascertain whether 0, 1, or 2 copies of the insertion were present. Results: There was a decrease (p = 0.018) in the proportion of PSS patients with the deleted/deleted genotype. There was no association with specific BV6S7 alleles or genotypes with either the PSS group or the hypergammaglobulinaemic subgroup. There were no significant differences in haplotype frequencies after Bonferroni correction. Conclusions: A reduced proportion of patients with PSS have the deleted/deleted genotype. Eighty nine per cent of PSS patients have at least one extra germline copy of BV13S2*1. This may relate to previous observations of increased BV13 specific T cells and mRNA in the salivary glands.